PELESTARIAN TARI PIRING DI ATEH TALUA DALAM SANGGAR SINAR GUNUANG KANAGARIAN BATU BAJANJANG KECAMATAN LEMBANG JAYA KABUPATEN SOLOK - Rima Silvia; Afifah Asriati; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2013)
Abstract This article aims to describe the existence of traditional dance called Tari Piring di Ateh Talua in hall of Sinar Gunuang, Batu Bajanjang town, districk Lembang Jaya, in sub province of Solok. Research used the qualitative with descriptive method. Technique collecting data held by doing study on library, observation, interview and documentation. Technique of the data analysis held by classified the data based on the conceptual framework. Result of the research showed that Tari Piring di Ateh Talua survived by teaching and sharing. Teaching of Tari Piring di Ateh Talua was doing by traditional teaching of the teacher and student. Besides that, sharing is held by performing and presenting the dance in traditional ceremony like Batagak Gala, competition, and welcome dance. Kata kunci: Pelestarian, Tari, Piring di ateh Talua